Tata kelola informasi dan gerakan sosial sertifikasi - Purnomo, H. (2004)
Forest certification remains an important requirement in working towards sustainable forest management. The Indonesian Eco-labeling Institute (LEI) was a foundation, which had developed a certification system and accredited certification bodies in Indonesia. However, there has been a call for LEI to be more democratic in its decision making processes, as well as, facing the question of credibility in its ability to represent all Indonesian certification. In response to this situation, LEI is now in the process of moving from a foundation to a constituent-based organization (CBO). This institutional change will adjust the dynamic flow of information to and from LEI. In general, information does not flow freely, it flows according to people’s interests and social, economic and political situations. If LEI is able to govern the flow of this information properly then a social movement of certification may well emerge. Constituents with a high network quotient may then endorse this social movement. This paper also suggests a matrix organization for the internal structure of LEI.